Strategies of non-OECD gas producers in the Atlantic and the Middle East - Hallouche, H; Train, B (Oxford Institute for Energy Studies, 2006)
The international gas market is undergoing a quiet revolution, by any standard. Gas is the most environmentally friendly fossil fuel and is the most efficient for power generation. This has increased consumption for gas dramatically, as in the image of the Dash for Gas in the UK. At the same time, domestic production has reached its limitations in many consuming markets. The resulting growth in the international trade of the fuel of the twenty-first century comes at a time of high oil prices and at a time of reform and liberalisation of the gas and electricity markets in many consuming markets, notably the EU.